INCOME ANALYSIS OF BALI DUCK FARMING WITH INDIGOFERA LEAF JUICE (Indigofera zollingeriana) - V. E., Putra; Putri, B.R.T.; Suarta, G. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the income of Bali Duck farming by giving indigofera leaf juice ( Indigofera z ollingeriana ). This research was conducted for two months at Sesetan Farm, Faculty of Animal Science, Udayana University, Denpasar. The design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications with 120 bali ducks used. The treatments were drinking water without indigofera leaf juice which was used as a control (A), drinking water given indigofera leaf juice as much as 2% (B), drinking water given indigofera leaf juice as much as 4% (C) drinking water given juice indigofera leaves as much as 6% (D). The observed variables include income analysis based on costs, revenues, income, R/C ratio and BEP. The results of the income analysis showed that ducks with 4% indigofera leaf juice gave the best results with an income of Rp 406,561,-/period with an R/C ratio of 1.225. BEP of production units is 36,059 kg live ducks, BEP selling price of ducks per kg is Rp 40,799,-/kg live weight, and BEP for revenue is Rp 1,802,950/period. Based on the results of the study, it can be concluded that Bali duck farming by giving indigofera leaf juice ( Indigofera z ollingeriana ) can increase the income of farmers. Keywords: Income analysis, duck and indigofera leaf juice